Relationship between attributional style, perceived control, self-esteem, and depressive mood in a nonclinical sample: A structural equation-modelling approach - Ledrich, Julie; Gana, Kamel (Psychology and psychotherapy, 2013)
Background. The aim of this study was to examine the intricate relationship between some personality traits (i.e., attributional style, perceived control over consequences, self‐esteem), and depressive mood in a nonclinical sample (N= 334). Method. Structural equation modelling was used to estimate five competing models: two vulnerability models describing the effects of personality traits on depressive mood, one scar model describing the effects of depression on personality traits, a mixed model describing the effects of attributional style and perceived control over consequences on depressive mood, which in turn affects self‐esteem, and a reciprocal model which is a non‐recursive version of the mixed model that specifies bidirectional effects between depressive mood and self‐esteem. Results. The best‐fitting model was the mixed model. Moreover, we observed a significant negative effect of depression on self‐esteem, but no effect in the opposite direction. Conclusions. These findings provide supporting arguments against the continuum model of the relationship between self‐esteem and depression, and lend substantial support to the scar model, which claims that depressive mood damages and erodes self‐esteem. In addition, the ‘depressogenic’ nature of the pessimistic attributional style, and the ‘antidepressant’ nature of perceived control over consequences plead in favour of the vulnerability model. Practitioner Points • Pessimistic explanatory style and perceived control over consequences were found to be depressogenic, acting as vulnerability factors for depression. • Depression was found to erode and damage self‐esteem (i.e., ‘scarring’ effect).